A cross-sectional study of nutritional status of children below 6 year age group in urban Hyderabad - M A Thaher; M.Hima Bindu; Rajesh Neeluri; Krishna Prakash Joshi (International Journal of Health and Clinical Research, 2021)
Background: Malnutrition is a curse of developing and under developing countries which is blockage in their physical, mental & social development. It is part of Poverty –Diseases- Malnutrition vicious cycle. Hence present study was conducted to know the malnutrition status of below 6 years children in tertiary care urban centre. Material & methods: A cross-sectional observational study was conducted in urban field practice area of Deccan College of Medical Sciences- Department of Community Medicine covered by 24 ICDS centres. From each ICDS centre,20 children were selected randomly as study subjects. so that 480 children were covered from 24 ICDS centres of Deccan College of Medical Sciences field practice area. Results: Maximum number of children was in the age group of 13-24 months i.e. 155 (32.3 %) and least number of children was observed in the age group of 61-72 months i.e. 12 (2.5%).Majority (53.3%) of subjects belonged to upper lower socio – economic status according to modified Kuppuswamy classification. Prevalence of overall malnutrition for underweight, stunting and wasting is found to be 19.4%, 41.3% and 16.5% respectively according to WHO classification. Conclusion: Health education and awareness about nutrition to parents and first line workers can make more difference in the nutrition status of children.